Locus specificity of polymorphic alleles and evolution by a birth-and-death process in mammalian MHC genes - Gu, X; Nei, M (Molecular biology and evolution, 1999)
We have conducted an extensive phylogenetic analysis of polymorphic alleles from human and mouse major histocompatibility complex (MHC) class I and class II genes. The phylogenetic tree obtained for 212 complete human class I allele sequences (HLA-A, -B, and -C) has shown that all alleles from the same locus form a single cluster, which is highly supported by bootstrap values, except for one HLA-B allele (HLA-B*7301). Mouse MHC class I loci did not show locus-specific clusters of polymorphic alleles. This was considered to be because of either interlocus genetic exchange or the confusing designation of loci in different haplotypes at the present time. The locus specificity of polymorphic alleles was also observed in human and mouse MHC class II loci. It was therefore concluded that interlocus recombination or gene conversion is not very important for generating MHC diversity, with a possible exception of mouse class I loci. According to the phylogenetic trees of complete coding sequences, we classified human MHC class I (HLA-A, -B, and -C) and class II (DRB1) alleles into three to five major allelic lineages (groups), which were monophyletic with high bootstrap values. Most of these allelic groups remained unchanged even in phylogenetic trees based on individual exons, though this does not exclude the possibility of intralocus recombination involving short DNA segments. These results, together with the previous observation that MHC loci are subject to frequent duplication and deletion, as well as to balancing selection, indicate that MHC evolution in mammals is in agreement with the birth-and-death model of evolution, rather than with the model of concerted evolution.